Analysis of Contact Resistance Test for PMT Bay Kuningan II 70KV at Sunyaragi Substation - Rezza Badruzzaman; Arnisa Stefanie (Muhammadiyah University, Sidoarjo, 2021)
Electrical energy is included in the primary needs of humans in this era, where in this modern era, almost all equipment is electronic based so that the need for electrical energy is very large. In Indonesia, there is a company that is in charge and responsible for processing and distributing electricity to the public, namely PLN or more specifically the Substation. To distribute electricity at this substation, there are primary equipment that functions as a transmission regulator, one of which is a power breaker (PMT). PMT is one of the important assets in the reliability of the electricity system at the substation, so periodic testing and maintenance is very necessary. Testing and maintenance on PMT are very diverse from insulation resistance testing, simultaneous testing (Breaker Analyzer), SF6 gas characteristic testing, and PMT contact resistance testing. This contact resistance test is carried out to determine the resistance value of the PMT contact, from the resistance value obtained it can also be seen for the value of the power loss generated by the PMT when operating.